The Role of Motivation in Technical Translation Teaching to Master Degree Students; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Tarasova E. S. Ekaterina Sergeevna (2015, 2015)
Title screen